Misconceptions of Elementary School Students about Fractions - Fittriyanti, Fittriyanti; Zubainur, Cut Morina; Anwar, Anwar; Novianti, Novianti (International Conference on Elementary Education, 2020)
Misconception is a serious problem in the teaching and learning process, misconceptions experienced by students will result in concept errors at a later stage. So it will affect student learning outcomes. The purpose of this study was to determine the type of misconception about fractions experienced by elementary school students. This study involved 11 students in grade IV of SD Negeri 9 Jangka, 2018/2019 school year consisting of 5 boys and 6 girls. Student misconceptions are identified through diagnostic tests that are reinforced by interviews. The results showed the types of misconceptions experienced by students, among about 1) Students compare two fractions by comparing the numerator with the numerator and the denominator with the denominator, in this case students have a tendency to transfer the concept of natural numbers into fractions. 2) Students have a misunderstanding when the teacher represents fractions on the number line, The teacher explains that the fraction that is on the left has a smaller value than the fraction on the right, so students think that the fraction is left on the problem always has a smaller value